Morphofunctional evaluation of liver grafts obtained from standard donors and expanded criteria donors - M. Sh. Khubutiya; L. N. Zimina; I. E. Galankina; V. A. Gulyaev; M. S. Novruzbekov; O. D. Olisov; K. M. Magomedov (Трансплантология (Москва))
Donor organ shortage stimulated an active use of donors with expanded evaluation criteria. The main evaluation method was a histological examination of liver graft biopsy specimens before (time-zero biopsy) and after reperfusion (time-1 biopsy). Severe ischemic and reperfusion injuries among recipients who received a liver graft made 20.4% and 16.6% respectively. The study showed no impact of small droplet, medium droplet, or even large droplet steatosis (less than 50%) on graft reperfusion injury.